Why Are Interest Rates on Bank Deposits so Low? - Ramona Busch; Christoph Memmel (Credit and Capital Markets – Kredit und Kapital, 2021)
Using granular data of German banks for the 2003 to 2018 period, we analyze the determinants of bank rates on retail deposits. We find that a bank's rate on sight deposits is especially low if the bank operates in rural districts, if it is not exposed to strong competition and if it provides much service. Regarding the rates on term deposits, we find that the bank's cost situation plays a role: if the bank's costs are high, its deposit rates are low. By transferring concepts from portfolio theory to the pass-through topic, we show that replicating portfolio approaches are often equivalent to regression approaches and that, under some assumptions, the classical regression approach corresponds to a replicating portfolio approach.
Keywords: G21; 330; Pass through; bank deposits; replicating portfolio approach; G 21